Relasi Suami-Istri: Telaah Kompilasi Hukum Islam Perspektif Teori Mubadalah - Miswanto; Arif Fikri; Edi Susilo (CV. Creative Tugu Pena, 2024)
The concept of husband-wife relations in the KHI which states that the husband is the head of the family and the wife is the housewife has carried a negative stigma. Husbands feel entitled to everything, do not provide freedom for their wives, religious arguments are often used to justify arrogance so it is not surprising that domestic violence (KDRT) often occurs. This concept in today's social situation is seen as having given rise to legal injustice and is irrelevant, especially from a gender justice perspective. The aim of this research is to further examine the concept of husband-wife relations in the KHI from the perspective of mubjadi theory. Practically, this study is expected to give birth to a new paradigm for the concept of husband-wife relations and can be accommodated in the articles of the KHI. The type of research used is library research. This research is qualitative in nature using descriptive-qualitative techniques to clearly describe the concept of husband-wife relations in KHI and then analysis is carried out using mubjadi theory. The results of the research conclude that the concept of husband-wife relations in the KHI, namely article 79 paragraph 1 concerning the position of husband and wife and articles 80, 84 and 152 concerning nusyuz in the perspective of Mubjadi theory is considered gender biased because it is not equal and not egalitarian. The concept of husband-wife relationship must be built on the basis of pairing (zawaj), mutuality (mubjadi), partnership (mu'awanah), and cooperation (musyarakah). Therefore, it is necessary to immediately reconceptualize KHI so that the concept of husband-wife relations is fair and can support the creation of a sakinah mawaddah and warahmah family.